Politics of History of the Third Polish Republic: ReOrientation (1989–2007) - Andrzej Nowak (Review (Institute of National Remembrance), 2020)
This article summarises the concepts behind the direction of Polish politics towards Ukraine, Lithuania, Belarus and Russia in placing Poland’s new international relations in Central and Eastern Europe due to its historical ties with the countries of the region. A significant verbal role was played by the reception in Polish politics of the doctrine of Mieroszewski and Giedroyc-the so-called ULB (Ukraine–Lithuania–Belarus). It assumed the establishment of special relations with these countries, and, at the same time, waiving claims to territories lost by Poland after 1939. The application of this idea was conditioned by the internal political dynamics of Ukraine, Belarus, Russia, and Lithuania, and their mutual relations that determined the effectiveness of this doctrine. A key role in shaping Poland’s policy towards these countries was played by an “historical factor”-the exchange of mutual declarations concerning the past; this sometimes included the transmission of documentation-for instance the Katyn massacre evidence documents were transferred to Poland in 1990 by the Russian authorities. These actions served as tools of political rapprochement, and they sometimes resulted in opening the way to re-examine previous historical interpretations (especially in Polish–Lithuanian and Polish–Ukrainian relations). The question of investigating the crimes of the USSR against Poles, including above all the Katyn massacre (1940), played an important role in the rapprochement in Polish–Russian relations in the early period of President Yeltsin’s rule. One of the repercussions of implementing this concept and its conciliar priorities in Polish foreign policy and in its internal formal discourse was the suppression of some recently recreated areas of collective memory and currents of historical discourse; this especially concerned Polish–Ukrainian relations, in the context of, among others, the massacre in Volhynia in 1942–1943. Another result was transferring possible settlements to the responsibility of the state and the Polish community-a particular example of which was a resolution of the Polish Senate concerning Operation “Vistula” (Akcja “Wisła” in 1947) that was adopted in 1990.